Analysis of leprosy in the northeast region of Brazil in the period of 2017-2021 (Research, Society and Development, 2022)
Objective: evaluate the epidemiology of leprosy cases in the state of Rio Grande do Norte (RN), in comparison with other states in the northeast of Brazil, from 2017 to 2021. Methodology: this is a descriptive and quantitative study realized by  data collected in the Department of Informatics of the Unified Health System (DATASUS). The study occurred with the analysis of informations about confirmed cases from leprosy at RN and others states from northeast of Brazil in the period of 2017 until 2021, evaluating age, sex, breed and year of diagnostic. Results: there were 62,335 cases of leprosy in the northeast, in the analyzed period, with the highest incidence  in the state of  Maranhão with 26,91% of cases whilst RN had about 1,99% of cases. This disease was predominant in brown people under 60 years old, regardless of sex. Conclusion: therefore, in the northeast, RN did not have the highest number of cases, however it is possible that there are underreported cases, triggering a reduction in public policies for this disease. Therefore, in the face of this reality, there is still a need for health actions that train professionals and students in the health care area to properly carry out the screening, notification and early diagnosis of this disease.